Health-related quality of life and disease progression in pulmonary arterial hypertension patients: a 3-year study. Issue 3 (23rd August 2021) - Halimi, Laurence; Suehs, Carey M.; Marin, Gregory; Boissin, Clement; Gamez, Anne-Sophie; Vachier, Isabelle; Molinari, Nicolas; Bourdin, Arnaud
Objectives: The role of health-related quality of life (HRQoL) and psychological variables in pulmonary arterial hypertension (PAH) progression remains poorly quantified. We aimed to investigate the relationship between disease progression in PAH patients and HRQoL and psychological characteristics. Methods: A 3-year longitudinal cohort was initiated. Patients with stable PAH (groups I–IV ineligible for angioplasty/endarterectomy) were included (n=55). Standard clinical variables, including invasive haemodynamic parameters, were prospectively recorded. A battery of questionnaires was used to characterise the psychological status of patients upon study initiation, and HRQoL was quantified using the SF-36 Questionnaire every 3 months for 24 months, and then again at 36 months. Guideline-defined disease progression and progression-free survival were recorded for 36 months. Measurements and main results: Psychological distress was highly prevalent at baseline. The Physical Component Summary (PCS) and the Mental Component Summary (MCS) of the HRQoL were poor (PCS=37.13±8.18; MCS=42.42±10.88) but stable over 3 years of follow-up. Among PCS subscales, Physical Functioning (PF) (p=0.012) was identified as being independently associated with disease progression (Cox survival model), along with mean pulmonary arterial pressure (p=0.003) and cardiac output (p=0.005). Depression was the unique independent psychological characteristic associated with PF (p=0.0001). Conclusions: PAH patients have poor HRQoL. In addition to already known criteria related to disease severity, the HRQoL PF subscale is independently associated with disease progression in PAH. This may be explained by depression. Baseline subscale SF-36 Physical Functioning questionnaire for PAH patients is independently associated with disease progression at 3 years. HRQoL should be considered as a complement to risk assessment criteria. https://bit.ly/3mrZhHT